“I would like to use it more effectively…” nursing student’s experiences with NANDA-I nursing terminology: a qualitative descriptive study - Turgay Yalcinkaya; Erkan Ünsal; Ayşegül Dönmez; Sebnem Cinar Yucel (BMC Nursing)
Abstract Background Standardized nursing terminologies play a crucial role in describing and documenting nursing care. For students, learning the components of the NANDA-I terminology—such as defining characteristics and related factors—accurately is essential for determining nursing diagnoses. However, there is a notable lack of qualitative studies investigating Turkish nursing students’ experiences with these terminologies. This study aimed to explore nursing students’ experiences regarding NANDA-I nursing terminology. Methods This descriptive qualitative study was conducted with 29 second-, third-, and fourth-year nursing students. Data were collected through face-to-face, in-depth, and semi-structured interviews between June 2023 and December 2023. Content analysis was used to analyze the data. Results Content analysis revealed four main themes: (a) knowledge and awareness, (b) the facilitating effect of NANDA-I on patient care, (c) improvement of NANDA-I terminology training, and (d) challenges in utilizing NANDA-I. Conclusions The findings of this study offer recommendations for nursing educators to make adjustments to the educational curriculum concerning NANDA-I terminology. Developing nursing education curricula is crucial to help students gain a better understanding of NANDA-I terminology and to utilize it effectively in clinical practice. Clinical trial number Not applicable.